The iconic representation of iconic mosque: case study of Masjid Zahir, Alor Setar, Kedah - Ibrahim, Mansor (s.n, 2012)
Great mosques have always contributed towards the establishment of Islamic city through the past centuries. The religious practices of Islamic teachings towards nationhood, exemplify this perspective and the idea of mosque has received functional acclaimed as not only religious platform, but also as community development. However, such attention to issues of form, function and aesthetics, are tested and addressed as crucial questions about the Muslim public engagement with mosque. This research suggests that the existence of historic state mosque as ‘iconic monumental structure’ is regarded as symbolic through the continuity of Islamic nationhood performance in the community. Empirically, this paper investigates the representation of the urban city dwellers preference towards the continuation of mosque as nationhood integration and comparing with the adjacent iconic building; Balai Besar. The research was done to relate the building to the backgrounds of the cultural and societal context of the days before (specifically during the era of the Sultanate and Colonialism) and after independence. This colonial mosque is a building of architectural excellence and unexceptional historical value to the state because of the major roles it played as a venue for historical events and as an architectural symbol that reflected the Islamic rulings of Kedah’s royalty. Although this current research managed to document information on the situation and architectural aspects of the building, this alone is not enough to depict all information needed for preventing the mosque from dilapidation. Future generations must keep on inspecting every aspects of the building to ensure that the required data for restoration and maintenance work is not lost, along with the movement of the country towards globalization and modernization.